1999
DOI: 10.1034/j.1600-0412.1999.780401.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐induced hypertension and insulin resistance, evidence for a connection

Abstract: PIH, the most common complication of pregnancy, remains a major source of maternal-child morbidity and mortality. Yet the etiology of this disorder is still little understood. There is now a growing body of evidence linking PIH and insulin resistance. Both proteinuric and non-proteinuric PIH predict future essential hypertension, and to a lesser extent, diabetes, disorders strongly related to glucose intolerance and insulin resistance. PIH is associated with diabetes, occurring in up to 50% of diabetic pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 322 publications
(486 reference statements)
0
21
0
Order By: Relevance
“…Martinez et al found higher plasma in- sulin levels in women with PIH despite normal glucose tolerance (16). The relationship appears strongest in Caucasians and East Asians (15). This causes secondary hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinez et al found higher plasma in- sulin levels in women with PIH despite normal glucose tolerance (16). The relationship appears strongest in Caucasians and East Asians (15). This causes secondary hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Innes and Wimsatt have recently reviewed the extensive evidence for a link between PIH and insulin resistance (15). Innes and Wimsatt have recently reviewed the extensive evidence for a link between PIH and insulin resistance (15).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance (ie, resistance to insulin-stimulated glucose uptake) is generally considered the primary defect underlying IRS and is a cardinal feature linking IRS with the development of atherosclerosis and CVD 11,20. Insulin resistance is a strong independent risk factor for CVD in both diabetic21 and nondiabetic individuals21–27 and has been causally linked to elevated blood pressure,13,28,30 dyslipidemia,13,31,32 inflammation,19,33 impaired fibrinolysis, 13,19 endothelial dysfunction,13,19,32,34 sympathetic activation, 13,29,34 and other indices of CVD risk 13,18,19. Insulin resistance increases dramatically with menopause,1,6,7,35,36 and is considered to be a key factor underlying the abrupt increase in CVD risk among women after menopause 6,36,37…”
mentioning
confidence: 99%
“…Patients with gestational diabetes mellitus (GDM) are more insulin resistant compared to control pregnant subjects with NGT [8]. GH has been associated with hyperinsulinemia [2,9,10,11,12,13]. No similar associations were reported regarding the relationship between PE and IR either in normoglycemic pregnancies or in GDM [14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 96%
“…Several studies suggest that glucose intolerance and insulin resistance (IR) may play a role in the etiology of these diseases as the incidence of hypertensive disorders is twice as high in pregnancies of glucose-intolerant women compared to women with normal glucose tolerance (NGT) [2]. IR and related hyperinsulinemia are associated with essential hypertension in nonpregnant individuals [3].…”
Section: Introductionmentioning
confidence: 99%